Answer:
The steps are outlined in the explanation below.
Explanation:
The average velocity is derived midpoint from the initial to the final velocity. Here is the proof:
Find the total displacement:
let the displacement be given by the letter s
Then since the average velocity is defined as: [tex]v_{av} = \frac{x - x_{0} }{t - t_{0} }[/tex]
where t = final time
t₀ = initial time
v = final speed
v₀ = initial time
where x denotes the position, then
[tex]v_{ave} = \frac{v+v_{0} }{2}[/tex]
where v = [tex]\frac{dx}{dt}[/tex] and dx = change in distance with respect to time.